The effect of 12-week long exercise intervention, and 2-weeks of detraining period on lower limbs strength parameters and postural stability in older adults: a linear mixed model analysis - Svobodová, Lenka; Sebera, Martin; Vodička, Tomáš; Svobodová, Aneta; Horáková, Andrea; Stračárová, Nikola; Svobodová, Šarlota; Eclerová, Veronika; Vespalec, Tomáš; Kasović, Mario; Paludo, Ana Carolina; Bienertova-Vasku, Julie; et al. (BMC geriatrics, 2025)
BACKGROUND: Muscle strength and postural control are essential components for performing daily living activities, particularly in older adults, and can therefore serve as screening tools for assessing fall risk in this population. METHODS: The aim of this quasi-experimental study was to evaluate the impact of a 12-week exercise intervention followed by a 2-week detraining period on lower limb strength and postural stability in older adults. The study involved 38 community-dwelling participants of Central European origin over 60 years of age. Participants underwent the measurements consisting of assessments of knee flexors and extensors strength (isokinetic dynamometer, 90° range of motion, 60°/s angular velocity, Humac Norm CSMI, Stoughton MA, USA), toe grip strength (toe grip dynamometer, Takei Scientific Instruments, Niigata, Japan), and postural stability (narrow stand, 30 s, Kistler, Switzerland). Testing was repeated three times during the study (pre-intervention, post-intervention, and post-detraining). Participants were separated into 3 groups according to the type of training: resistance training group (n = 13), proprioceptive training group (n = 14), and endurance training group (n = 11). The intervention program lasted 12 weeks, two 60-min sessions per week. A linear mixed model (LMM) predicted a change in postural stability after the resistance, proprioceptive, and endurance exercise interventions were applied. RESULTS: Results showed that knee extensor strength normalized to body mass significantly increased in the resistance training group post-intervention (p = 0.01). Toe grip strength was significantly higher after the intervention in the endurance training group (p = 0.02). A statistically significant increase in knee flexor strength was observed in the proprioceptive training group (p = 0.01). The 2-weeks detraining period revealed no statistically significant loss in training gains. The LMM found different predictions of postural stability changes related to knee extensor strength after each type of training intervention. The final LMM model explains well the variability of the dependent variable R2 = 0.866. CONCLUSIONS: These results highlight the unique characteristics of specific exercise interventions in enhancing muscular strength and postural stability, which are critical for fall prevention among older adults.
Keywords: Female; Linear Models; ženské pohlaví; Falls prevention; Resistance Training; svalová síla; Time Factors; časové faktory; lidé; cvičení; Exercise Therapy; Postural Balance; Aged, 80 and over; lineární modely; Muscle Strength; Middle Aged; Resistance training; Male; Aged; Postural balance; Muscle strength; Accidental Falls; terapie cvičením; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; úrazy pádem; Exercise; dolní končetina; Lower Extremity; odporový trénink; posturální rovnováha; Humans